2011
DOI: 10.1016/s1995-7645(11)60112-0
|View full text |Cite
|
Sign up to set email alerts
|

Enteric parasites prevalence at Saint Camille Medical Centre in Ouagadougou, Burkina Faso

Abstract: This study confirms that intestinal parasites are still a public health problem in Burkina Faso. To reduce the incidence of parasitic infections, it is necessary to promote the education of people so that they practice the rules of individual and collective hygiene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 18 publications
3
8
0
Order By: Relevance
“…This prevalence of intestinal parasitism is high compared with previous findings in Burkina Faso. Other authors reported 23.8 % in Bobo-Dioulasso [ 17 , 23 ] 52.4 and 60.8 % in Ouagadougou [ 15 , 16 ]. The difference could be due mainly to coproparasitological techniques used.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This prevalence of intestinal parasitism is high compared with previous findings in Burkina Faso. Other authors reported 23.8 % in Bobo-Dioulasso [ 17 , 23 ] 52.4 and 60.8 % in Ouagadougou [ 15 , 16 ]. The difference could be due mainly to coproparasitological techniques used.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the epidemiology of intestinal parasitism is very wide and is significantly different between sahelian area (38.9 % in the Sahel) and humid area (65.8 % in the East) [ 13 ]. In the capital city of Ouagadougou, a prevalence of 60.82 and 52.47 % have been previously reported respectively by Ouermi et al ., [ 15 ] and Karou et al ., [ 16 ]. In Bobo-Dioulasso, economic capital of the country, the prevalence of intestinal parasites was 23.8 % [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…In Burkina Faso, where polyparasitism is common [ 16 , 17 ], a deeper understanding of multiple species parasite infections is key for disease control and the reduction of the burden due to these (co-) infections. Whilst health data among under 5-year-old children are collected during national Demographic and Health Surveys (DHS) in Burkina Faso, such as anaemia and Plasmodium spp.…”
Section: Introductionmentioning
confidence: 99%
“…The evidence strongly pointed to the helminthes as the number one problem, particularly in developing countries like Burkina-Faso and Botswana (Emongor, 2006;Karou et al, 2011). The parasitic contamination of water resources and soil reflects the epidemiological status of the local community (Carabin et al, 2009).…”
Section: Discussionmentioning
confidence: 99%